216 IMPROVING INPATIENT INFLUENZA VACCINATION RATES—THE VALUE OF AN ELECTRONIC PATIENT RECORD REMINDER SYSTEM. (18th November 2021) - Chapman, L; Piggott, R S; Kelly, M; O'Connell, B; Bannon, C; Cunningham, C; Briggs, R
Abstract: Background: Influenza vaccination, particularly for vulnerable, older adults, will have added importance this winter given the possibility of further waves of COVID-19 pandemic. Previous interventions at the study site noted poor awareness on the need for inpatient Influenza vaccination 1 . This study examines a vaccination reminder process using an electronic patient record (EPR) to identify high-priority eligible inpatients. Methods: The study site is a 900-bed university teaching hospital with all clinical notes accessed via an EPR. We included a convenience sample of 750 adults aged≥50 years (mean age 75.9 +/− 0.4 years, 48% female) and high-priority for influenza vaccination (Age > 65 years and/or length of stay (LOS) >30 days) from October 1 st 2020 to January 12 th 2021. A live electronic dashboard identified eligible inpatients for vaccination, prompting vaccination reminders to the clinical teams via the antimicrobial pharmacist. Data was collected retrospectively. Logistic regression models reporting odds ratios were used to assess the association of these reminders with vaccine uptake. Results: Over one third (35%, 264/750) of high-priority patients received the Influenza vaccine while inpatients, including 40% aged ≥80 years. The reminder was sent on 41% (305/750) of patients and was associated with an almost 50% higher likelihood of vaccination after adjusting for other covariates (Odds Ratio 1.48 (95% CI 1.00–2.20); p = 0.048). Other factors independently associated with vaccination were advancing age (Odds Ratio 2.69 (95% CI 1.12–6.47) for age ≥ 80 years); LOS (4% higher likelihood of vaccination for every additional day in hospital) and admission under geriatric medicine (Odds Ratio 3.71 (95% CI 2.45–5.62) when compared to other specialities). Conclusion: Our study shows relatively low uptake of inpatient Influenza vaccination and strategies to improve uptake are required. Reminders sent to clinical teams using the EPR appear to be an effective means of increasing Influenza vaccination and should be considered as part of this year's inpatient vaccination drive.